Gene rearrangement detection by next-generation sequencing in patients with non-small cell lung carcinoma - Brisudova, Aneta; Skarda, Jozef (Biomedical papers, 2020)
Non-small cell lung carcinoma (NSCLC) is the leading cause of cancer-related deaths worldwide. Various molecular markers in NSCLC patients have been developed, including gene rearrangements, currently used in therapeutic strategies. With increasing number of these molecular biomarkers of NSCLC, there is a demand for highly efficient methods for detecting mutations and translocations in treatable targets. Those currently available U.S. Food and Drug Administration (FDA) approved approaches, for example imunohistochemisty (IHC) and fluorescence in situ hybridization (FISH), are inadequate, due to sufficient quantity of material and long time duration. Next-generation massive parallel sequencing (NGS), with the ability to perform and capture data from millions of sequencing reactions simultaneously could resolve the problem. Thanks to gradual NGS introduction into clinical laboratories, screening time should be considerably shorter, which is very important for patients with advanced NSCLC. Moreover, only a minimum sample input is needed for achieving adequate results. NGS was compared to the current detection methods of ALK, ROS1, c-RET and c-MET rearrangements in NSCLC and a significant match, between IHC, FISH and NGS results, was found. Recent available researches have been carried out on a small numbers of patients. Verifying these results on larger patients cohort is important. This review sumarizes the literature on this subject and compares current possibilities of predictive gene rearrangements detection in patients with NSCLC.
Keywords: non-small cel lung carcinoma; gene rearrangement; next-generation sequencing; immunohistochemistry; fluorescence in situ hybridization